C3G promotes bone marrow adipocyte expansion and hematopoietic regeneration after myeloablation by enhancing megakaryocyte niche function - Óscar Herranz; Pablo Berrocal; Carmen Sicilia-Navarro; Cristina Fernández-Infante; Luis Hernández-Cano; Almudena Porras; Carmen Guerrero (Journal of Hematology & Oncology)
Abstract C3G, a Rap1 GEF, promotes megakaryopoiesis and platelet function. Using transgenic and knock-out mouse models targeting C3G in megakaryocytes, we investigated whether C3G also affects the niche function of megakaryocytes during bone marrow (BM) recovery after myeloablation induced by 5-fluorouracil (5-FU), or total body irradiation (TBI) followed by bone marrow transplantation. C3G promoted megakaryocyte maturation and platelet production during recovery, along with increased white and red blood cell counts and enhanced survival of female mice after repeated doses of 5-FU. Additionally, megakaryocytes favored adipocyte differentiation through a C3G-mediated mechanism, likely involving Fgf1. Changes in the number or behavior of BM megakaryocytes and adipocytes influenced the hematopoietic stem cell pool, with C3G promoting its bias towards the myeloid-megakaryocytic lineage in both 5-FU- and TBI-ablated models. Therefore, C3G could be a potential target in therapies aimed at enhancing hematopoiesis in patients undergoing chemotherapy and/or BM transplantation.